Perceived E-Service Quality In Online Shopping From Malaysian Customers\' Perspective - Namdari, Elham (2011)
The main aim of this research is to discover the most important factors influencing Malaysian consumers\' thought and opinions regarding the quality of e-services by understanding the aspects and characteristics, which influence these opinions in online shoppers.